Impact of molecular structure of smectogenic chiral esters (3FmX1X2r) on vibrational dynamics as seen by IR and Raman spectroscopy. Issue 5 (9th April 2019) - Drzewicz, Anna; Bombalska, Aneta; Tykarska, Marzena
ABSTRACT: Smectogenic chiral esters with three-ring rigid core were examined by infrared and Raman spectroscopy. These compounds differ in the type of chiral centre, length of non-chiral chain and substitution of phenyl ring by fluorine atoms. The influence of molecular structure on the type of handedness of helical structure, as well as the shift and split of absorption bands on IR and Raman spectra were determined. The change of the length of non-chiral terminal chain has the most significant influence on the type of helical twist sense. All considered structural elements of tested compounds have the biggest influence on the value of wavelength of vibrational bands related to the carbonyl group located in the rigid core. Graphical Abstract: